CHALLENGES OF HUMAN RIGHT TO EDUCATION: THE “COURSINHO POPULAR ENEM” EXTENSION PROJECT IN THE CONTEXT OF THE COVID-19 PANDEMIC. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
Education is a human and social right achieved after decades of struggle through social movements. Achieving education, it is also possible to conquer other rights, however, emerging countries like Brazil still need to advance a lot of policies to avoid educational inequality. The covid-19 pandemic showed how unequal the country is, especially in terms of education, which was left behind by the State, harming thousands of children and young people of school age. The university extension project “Cursinho Popular Enem”, taught by students from the State University of Minas Gerais, was a way of helping young people who are trying to enter universities through Enem. Thus, this study show education as a human and social right that needs to be promoted, even in the face of dire situations such as the covid-19 pandemic. Therefore, the aforementioned extension project was analyzed, using empirical research and literary review as methodology.Keywords: Education, Human Rights, Remote Teaching, Popular Course Enem.